2021
DOI: 10.3389/fpls.2021.655103
|View full text |Cite
|
Sign up to set email alerts
|

Major QTLs and Potential Candidate Genes for Heat Stress Tolerance Identified in Chickpea (Cicer arietinum L.)

Abstract: In the context of climate change, heat stress during the reproductive stages of chickpea (Cicer arietinum L.) leads to significant yield losses. In order to identify the genomic regions responsible for heat stress tolerance, a recombinant inbred line population derived from DCP 92-3 (heat sensitive) and ICCV 92944 (heat tolerant) was genotyped using the genotyping-by-sequencing approach and evaluated for two consecutive years (2017 and 2018) under normal and late sown or heat stress environments. A high-densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 69 publications
0
39
0
Order By: Relevance
“…Functional genomics facilitates the elucidation of the important role of candidate genes for expression of tolerance against abiotic stress in crop plants [ 172 , 173 , 174 ]. Among cool season grain legumes, five HSP90 candidate genes ( Ca_25811 , Ca_23016 , Ca_09743 , Ca_17680 and Ca_25602 ) have been identified in chickpea through RNA-sequencing analysis of leaf, flower and roots at different growth stages [ 166 ].…”
Section: Genomics Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional genomics facilitates the elucidation of the important role of candidate genes for expression of tolerance against abiotic stress in crop plants [ 172 , 173 , 174 ]. Among cool season grain legumes, five HSP90 candidate genes ( Ca_25811 , Ca_23016 , Ca_09743 , Ca_17680 and Ca_25602 ) have been identified in chickpea through RNA-sequencing analysis of leaf, flower and roots at different growth stages [ 166 ].…”
Section: Genomics Interventionsmentioning
confidence: 99%
“…Mining of the candidate genes for heat tolerance revealed 236 genes in 2.28 Mb (44.6–46.9 Mb) region in CaLG05 and 550 genes in 6.50 Mb (7.85–14.35 Mb) in CaLG06 in chickpea. Functional categorization showed association of many genes with biological processes (168 genes in CaLG05 and 365 genes in CaLG06) in the two genomic regions [ 172 ]. Gene ontology classification revealed that these putative candidate genes (11 in CaLG05 and 14 in CaLG06) known to function, directly or indirectly, as heat-stress response genes in several plant species.…”
Section: Genomics Interventionsmentioning
confidence: 99%
“…To develop trait associated markers, available genomic information on candidate regions for drought and FW was collected from previous studies and focused on the identification of major QTL regions [12,14,15,[18][19][20]. For drought, a total of 26 genes identified in the "QTL-hotspot" region containing 24 SNPs were used to develop molecular markers for use in early generation selection.…”
Section: Development Of Trait-associated Markersmentioning
confidence: 99%
“…As a result, 10 SNP panel for drought was developed and tested for early generation selection for the backcross progenies (Table 1). Similarly, for the development of FW markers, genomic information on candidate regions of QTL associated with FW resistance was assembled from the studies [18][19][20] (Table 1 and Table S1). We used these markers on the backcross progenies and validated their usefulness in chickpea breeding programs.…”
Section: Development Of Trait-associated Markersmentioning
confidence: 99%
See 1 more Smart Citation